Fenomena Jamaah Tabligh - Wirman, Hardi Putra (Alhurriyah, 2012)
The phenomenon of Tablighi Jamaat (JT) has long characterized the religious movements in the archipelago with some of the formal characteristics such as clothing abaya, pants hanging above the ankles, khuruj and others. Judging from the teachings and practices of worship or aqidah is not seen as a group of deviant groups. The study used three instruments, namely concepts, propositions and theories. The concept as an abstraction that is used by researchers to build a building block (limit) in building propositions and theory. The proposition is a statement about the nature of a social reality that can be observed symptoms. While the theory is a series of interrelated propositions that can be used to explain and predict social phenomena. From the results of the study can be described that their exclusivity over imaged khuruj khuruj ala Muhammad Ilyas, their leaders and not khuruj ala Allah. Then in a special ritual in this pilgrim center there are things that portray acts of heresy seen widespread activities of prayer, prayer and bermunajat in front of the tomb or tombs. This phenomenon is exacerbated by the claims of those who just replenish themselves with "book Fadhail" by Sheikh Zakaria. Surely this is a bad precedent for the development of science.